2014
DOI: 10.3109/19396368.2014.900832
|View full text |Cite
|
Sign up to set email alerts
|

Successful pregnancy after SrCl2oocyte activation in couples with repeated low fertilization rates following calcium ionophore treatment

Abstract: This report describes a successful pregnancy and delivery following oocyte activation with strontium chloride (SrCl2) in couples with repeated complete fertilization failure or low fertilization rates even after calcium ionophore treatment. Eight infertile couples who showed complete fertilization failure or low fertilization rates after conventional intracytoplasmic sperm injection (ICSI) and calcium ionophore treatment. When the results of fertilization were not satisfactory in the cycles, the oocytes were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…In contrast, the efficiency of Sr 2+ in activating human oocytes is still debatable (Yanagida et al 2006, Kim et al 2015. Several authors described the efficiency of Sr 2+ in 'rescuing' human oocytes that failed to fertilize after ICSI (Kyono et al 2008, Kim et al 2014. On the contrary, other authors did not find that Sr 2+ stimulated Ca 2+ oscillations even after several hours of measurements (Rogers et al 2004, Lu 2015.…”
Section: +mentioning
confidence: 82%
“…In contrast, the efficiency of Sr 2+ in activating human oocytes is still debatable (Yanagida et al 2006, Kim et al 2015. Several authors described the efficiency of Sr 2+ in 'rescuing' human oocytes that failed to fertilize after ICSI (Kyono et al 2008, Kim et al 2014. On the contrary, other authors did not find that Sr 2+ stimulated Ca 2+ oscillations even after several hours of measurements (Rogers et al 2004, Lu 2015.…”
Section: +mentioning
confidence: 82%
“…To date, Sr 2+ has been applied as an AOA method to overcome FF or low fertilization rates (Kyono et al , 2008; Kim et al , 2012, 2014) in several IVF centers. However, the efficiency and the exact mechanism of Sr 2+ as an activation agent in human oocytes remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, the technology of assisted oocyte activation (AOA) is frequently applied during ICSI, with the principle of inducing a Ca 2+ increase within the FF oocytes. Thus far, a number of physical, mechanical and chemical AOA methods have been evaluated, with successful oocyte activation and development to term after applying electrical pulses (Egashira et al , 2009), modified ICSI procedures (Tesarik et al , 2002), Ca 2+ ionophores (Heindryckx et al , 2008; Ebner et al , 2012; Vanden Meerschaut et al , 2014) and strontium chloride (SrCl 2 ) (Kim et al , 2012, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various methods have been employed to induce artificial calcium oscillations in mammalian oocytes in vitro and thereby provoke oocyte activation and embryo development. Electrical pulses [18], calcium ionophore [19], and strontium [20] are typically used as parthenogenetic agents, and it has been demonstrated that electrical pulses and calcium ionophore generate a single calcium elevation, whereas multiple calcium oscillations are induced by normal fertilization or strontium [20]. Moreover, there is some evidence that procaine is able to disregulate cytoplasmic calcium rise(s) in female gametes.…”
Section: Introductionmentioning
confidence: 98%